Ant Libraries: A Comprehensive Review of Their Versatility and Power - Upadhyay, Pritam (Journal of Advanced Research in Library and Information Science, 2023)
Ant libraries, a group of programming tools motivated by the resourcefulness of ants, have become quite well-liked in the software development industry. These libraries include a variety of features that speed up the development process and improve code effectiveness. This review article seeks to offer a thorough understanding of the various applications of Ant libraries, as well as their benefits and drawbacks. We explore numerous ant-inspired algorithms and how they help to address problems in the real world across many fields. This review aims to assist developers, researchers, fans in making the most of these fascinating tools by highlighting the most recent advancements and trends in ant library research. The main categories of Ant libraries are highlighted in this in-depth analysis, including ant colony optimisation (ACO) libraries, task schedulers with ant-inspired design, distributed systems management with ant algorithms. We investigate the optimisation of complex tasks by ant algorithms using pheromone-based strategies, intelligent exploration, trail reinforcement. We also demonstrate practical uses of Ant libraries in fields like data mining, network routing, finance, logistics. The paper goes into more detail about the benefits of Ant libraries, including their capacity for self-organization, decentralised decision-making, adaptability to dynamic environments. We do, however, also take into account potential drawbacks such difficulty in parameter adjustment and convergence rate. In addition, we offer implementation and usage hints for developers to maximise their use of Ant libraries. Finally, we discuss the most recent advancements and anticipated trends in the industry.